Baccharis nebularis (Asteraceae, Astereae): a new species of B. subgen. Tarchonanthoides sect. Curitybenses from the mountains of Southern Brazil - Heiden, Gustavo; Pirani, José Rubens (Phytotaxa, 2014)
Baccharis nebularis, a new species belonging to B. subgen. Tarchonanthoides sect. Curitybenses, is described, illustrated, and compared to B. chionolaenoides and B. curitybensis. A key for its identification is provided. The new species occurs in patches of cloud forest thickets mixed with high altitude tropical grasslands in the southern Brazilian mountains. Data on distribution and habitat, phenology, conservation status, as well as a list of specimens examined are also presented.